Quinone-Derived π-Extended Phenazines as New Fluorogenic Probes for Live-Cell Imaging of Lipid Droplets - de Moliner, Fabio; King, Aaron; Dias, Gleiston G.; de Lima, Guilherme F.; de Simone, Carlos A.; da Silva Júnior, Eufrânio N.; Vendrell, Marc (Frontiers in Chemistry, 2018)
We describe a new synthetic methodology for the preparation of fluorescent π-extended phenazines from the naturally-occurring naphthoquinone lapachol. These novel structures represent the first fluorogenic probes based on the phenazine scaffold for imaging of lipid droplets in live cells. Systematic characterization and analysis of the compounds in vitro and in cells led to the identification of key structural features responsible for the fluorescent behaviour of quinone-derived π-extended phenazines. Furthermore, live-cell imaging experiments identified one compound (P1) as a marker for intracellular lipid droplets with minimal background and enhanced performance over the lipophilic tracker Nile Red.